Pengaruh Implementasi Strategi Pemasaran Terhadap Peningkatan Nasabah Yang Menabung Pada Bank Nagari Syariah Cabang Padang - S. Syahril (Universitas Dharma Andalas, 2019)
The title of this study is: The Effect of Marketing Strategy Implementation on Increasing the Amount of Savings at Bank Nagari Syari’ah Padang Branch. The author is interested in researching this because in the banking world transactions, especially transactions at conventional banks by the ulama are stated to be usury with interest systems. This is because transactions at conventional banks are not preceded by a contract (agreement) between the bank and the customer, whereas in Islam every transaction must be a contract and a permit from both parties a transaction is declared lawful.In introducing Shari'ah banks to the community there are many problems and problems, especially the problem of public trust in Shari'ah banks which, not yet in accordance with Islamic Shari'a, because people admire the bank syari; ah only exchange clothes with conventional banks. To eliminate the perception of society like that, Islamic banks need to promote Shari'ah products offered by implementing marketing strategies based on Islamic Shari'a. One of the agencies that has the above problems is the Padang branch of the Syariah branch, where it is suspected that there is a lack of customers who save at the Padang branch of the Syariah Shari'ah Bank, because employees who have not mastered the marketing strategy related to the actual Shari'ah bank. To increase the number of customers who are saving nagari syariah banks, they recruit several employees who truly master the operational system of Islamic banks.The variables used in this study are the implementation of marketing strategies as independent variables (X) consisting of Products (X1), Price (X2), Promotions (X3) and the number of savers as dependent variables (Y). This independent variable will be tested against the dependent variable how much influence it has on the increase in the number of savers at the Padang branch of the Syariah Syariah Bank. The results of the study show that the product variable has a significant effect on the number of savers as well as the price variable which also has a significant effect on the number of savers in the nagari syariah padang bank. While the promotion variables and Place variables did not significantly influence the number of savers at the Padang branch Islamic bank. To measure this, we use quantitative research models that use multiple regression analysis.